Comportamento mecânico de misturas asfálticas recicladas a frio com emulsão e cimento portland - Brondani, Chaveli (2023)
Due to the increasing road traffic and environmental concerns, there is a growing demand for sustainable projects and materials. Cold recycled asphalt mixtures, owing to the mechanical complexity resulting from the variability of reclaimed materials and the diversity of stabilizing agents, have sparked interest in studies aimed at a deeper understanding of their mechanical behavior, given their promising viability. Accordingly, the main objective of this research was to evaluate the behavior of cold recycled asphalt mixtures composed of reclaimed materials stabilized with stone powder, cement, and emulsion used as a base layer. These mixtures consisted of two sources of RAP, one with neat binder and another with SBS-modified binder, Portland cement CP II-F, two emulsions RL-1C, conventional and rejuvenated, and stone powder. For the binder scale study, linear viscoelastic characterization of binders and asphalt pastes was performed, including the determination of the PG and analysis of the results of the MSCR and LAS tests. In the mixture stage, samples were molded and tested considering two major groups of tests. Firstly, index tests were conducted for dosage and quality control, including the RM, ITS and TSR. Subsequently, behavior tests were performed, including DM, uniaxial tensile-compression fatigue test, FN and HLWT. Mechanistic pavement analysis was also conducted using AEMC and LVECD software, simulated with the data obtained from mixture-level tests to better understand the behavior of the material and cold recycled asphalt mixtures within the pavement structure. The difference in sample preparation conditions at different levels, binder and mixture, significantly impacted the behavior of the materials, making it challenging to establish correlations between the levels, which is a limitation of the study. Cold recycled mixtures achieved typical values of hot asphalt mixtures in the MR test. In the TS test, all mixtures reached satisfactory tensile strength values, suitable for AASHTO M 352. The MID test showed that all mixtures met the AASHTO M 352 limits. This study reveals that these mixtures yield promising results in terms of permanent deformation and fatigue resistance. It also suggests that fatigue is the primary mode of failure in pavements with these mixtures. It is noteworthy that the results obtained in LVECD align with the analyses conducted in AEMC. As demonstrated by simulations, the use of cold recycled mixtures significantly reduces the tensile principal strain in the surface layer, resulting in better performance in terms of fatigue and permanent deformation.